257 Beef cows with atypical estrous cyclicity at puberty produced calves with deficits in pre-weaning muscling, metabolic indicators, and myoblast function but not in feedlot performance. (30th November 2020) - Swanson, Rebecca M; Gibbs, Rachel L; Cadaret, Caitlin N; Erickson, Galen E; Schmidt, Ty B; Cupp, Andrea S; Yates, Dustin T
Abstract: Economic beef production requires efficient growth. In our herd, cows were identified that exhibited irregular (start-stop) or absent (non-cyclic) pubertal estrous cyclicity prior to their 1st breeding season. These cows were sub-fertile but weaned heavier calves. Here, we determined if these calves possessed enhanced muscling and metabolic efficiency. Early muscle growth and metabolic indicators, feedlot performance, and carcass traits were evaluated in steer calves from cows that had exhibited normal (typical), start-stop, or non-cyclic pubertal estrous patterns. Start-stop and non-cyclic cows calved later (P < 0.05) than typical cows, but calf birthweights did not differ among groups. Weaning weights tended to be decreased (P = 0.09) in calves from start-stop and non-cyclic cows, but 205-d adjusted weaning weights did not differ. At 3 mo, body composition estimated by bioelectrical impedance revealed a tendency for reduced (P = 0.10) muscle mass in calves from non-cyclic and start-stop compared to typical cows. Plasma cholesterol, high-density lipoprotein, and triglyceride concentrations were reduced (P < 0.05) and glucose/insulin tended to be increased (P = 0.09) in calves from non-cyclic cows. Plasma urea nitrogen did not differ among groups. Ex vivo proliferation was greater (P < 0.05) for myoblasts isolated from calves of start-stop and non-cyclic compared to typical cows. Total oxidative metabolism did not differ but glycolysis was decreased (P < 0.05) in myoblasts from calves of non-cyclic cows. Feedlot average daily gain and dry matter intake did not differ during growing or finishing. Feed efficiency tended to be increased (P = 0.09) in calves from non-cyclic cows but not when normalized to dressing percentage. Hot carcass weight, dressing percentage, ribeye area, fat thickness, and marbling did not differ among groups. These findings indicate that atypical maternal estrous cyclicity at puberty reduced early muscle growth and metabolism in offspring but not feedlot growth or carcass merit. We speculate that early growth deficits are influenced by inflammatory changes.